Health and economic burden of disease of sugar-sweetened beverage consumption in four Latin American and Caribbean countries: a modelling study. Issue 2 (7th February 2023) - Alcaraz, Andrea; Bardach, Ariel Esteban; Espinola, Natalia; Perelli, Lucas; Rodriguez Cairoli, Federico; La Foucade, Althea; de Mello Vianna, Cid Manso; Guevara, Giovanni; Gittens-Baynes, Kimberly-Ann; Johns, Paula; Beharry, Vyjanti; Balán, Darío Javier; et al.
Abstract : Objective: Overweight and obesity are important contributors to the non-communicable disease burden. The consumption of sugar-sweetened beverages (SSBs) has been associated with an increased risk of type 2 diabetes mellitus (T2DM), cardiovascular disease, cancer and other conditions. The objective of this study was to estimate the burden of disease attributable to the consumption of SSBs and the costs to the healthcare systems in Argentina, Brazil, El Salvador, and Trinidad and Tobago. Design: Following a systematic review of models, a comparative risk assessment framework was developed to estimate the health and economic impact associated with the consumption of SSBs. Setting: Argentina, Brazil, El Salvador, and Trinidad and Tobago. Participants: Overall population. Primary and secondary outcome measures: The model estimated the effects of SSB consumption on health through two causal pathways: one mediated by body mass index (BMI) and health conditions associated with BMI and another that reflected the independent effects of SSB consumption on T2DM and cardiovascular diseases. Results: The model results indicated that for all four countries, in 1 year, SSB consumption was associated with 18 000 deaths (3.2% of the total disease-related deaths), seven million disease events (3.3% of the total disease-related events), a half-million DALYs and US2 billion in direct medical costs. This included 1.5 million cases of overweight and obesity in children/adolescents (12% of the excess weight cases) and 2.8 million cases in adults (2.8%); 2.2 million cases of type 2 diabetes (19%); 200 000 cases of heart disease (3.8%); 124 000 strokes (3.9%); 116 000 cases of musculoskeletal disease (0.2%); 102 000 cases of kidney disease (0.9%); and 45 000 episodes of asthma (0.4%). The Trinidad and Tobago population were the most affected by disease events. Conclusions: The study results indicate that the consumption of SSBs is associated with a significant burden of disease and death in Latin America and the Caribbean.